P2RX7 gene variants associate with altered inflammasome assembly and reduced pyroptosis in chronic nonbacterial osteomyelitis (CNO). - Charras, Amandine; Hofmann, Sigrun R.; Cox, Allison; Schulze, Felix; Russ, Susanne; Northey, Sarah; Liu, Xuan; Fang, Yongxiang; Haldenby, Sam; Hartmann, Hella; Bassuk, Alexander G.; Carvalho, Ana; et al. (Journal of Autoimmunity, 2024)
Chronic nonbacterial osteomyelitis (CNO), an autoinflammatory bone disease primarily affecting children, can cause pain, hyperostosis and fractures, affecting quality-of-life and psychomotor development. This study investigated CNO-associated variants in P2RX7, encoding for the ATP-dependent trans-membrane K+ channel P2X7, and their effects on NLRP3 inflammasome assembly. Whole exome sequencing in two related transgenerational CNO patients, and target sequencing of P2RX7 in a large CNO cohort (N = 190) were conducted. Results were compared with publicly available datasets and regional controls (N = 1873). Findings were integrated with demographic and clinical data. Patient-derived monocytes and genetically modified THP-1 cells were used to investigate potassium flux, inflammasome assembly, pyroptosis, and cytokine release. Rare presumably damaging P2RX7 variants were identified in two related CNO patients. Targeted P2RX7 sequencing identified 62 CNO patients with rare variants (32.4%), 11 of which (5.8%) carried presumably damaging variants (MAF <1%, SIFT "deleterious", Polyphen "probably damaging", CADD >20). This compared to 83 of 1873 controls (4.4%), 36 with rare and presumably damaging variants (1.9%). Across the CNO cohort, rare variants unique to one (Median: 42 versus 3.7) or more (≤11 patients) participants were over-represented when compared to 190 randomly selected controls. Patients with rare damaging variants more frequently experienced gastrointestinal symptoms and lymphadenopathy while having less spinal, joint and skin involvement (psoriasis). Monocyte-derived macrophages from patients, and genetically modified THP-1-derived macrophages reconstituted with CNO-associated P2RX7 variants exhibited altered potassium flux, inflammasome assembly, IL-1β and IL-18 release, and pyroptosis. Damaging P2RX7 variants occur in a small subset of CNO patients, and rare P2RX7 variants may represent a CNO risk factor. Observations argue for inflammasome inhibition and/or cytokine blockade and may allow future patient stratification and individualized care.
EVALuna2:558175